Comparison Between Traditional Ecological Knowledge of Coastal Villagers in Thailand and Scientific Ecological Knowledge Regarding Dugong - Rojchanaprasart, Natthita; Tongnunui, Prasert; Tinnungwattana, Wipawan (Kasetsart Journal of Social Sciences, 2014)
Previous studies of traditional ecological knowledge (TEK) of dugongs are sparse. Moreover, they did not compare TEK and SEK (scientific ecological knowledge) with statistical testing. Hence, this paper examined an equal proportion of TEK and SEK. The study covered five coastal communities in Trang province. In-depth interviews were used with coastal village elders by snowball sampling and with the team leaders of 5 coastal resource conservation groups by purposive sampling––a total of 40 interviewees. Qualitative analysis was applied by coding the knowledge issues of TEK for a comparison with the SEK that was derived from literature reviews and knowledge sharing in fora among villagers, academics, and other sectors. Consistent issues were scored as 1 and inconsistent issues were scored as 0, with the maximum score being 86. The proportion of TEK to SEK was tested by chi-square. The findings indicated that for the dugong morphology, the proportion of TEK was equal to SEK (p = .370). For dugong behavior, including swimming, breathing, feeding, and social behavior and communication, the proportion of TEK was equal to SEK (p = 1.000, .366, .715 and 1.000, respectively), while the proportion of TEK on breeding and parental care of calves was not equal to SEK (p = .034). In other words, the proportion of TEK on parental care of calves was equal to SEK (p = .405), while the proportion of TEK on breeding was not equal to SEK (p = .033). From the test results above, it could be concluded that the villagers’ traditional ecological knowledge regarding dugongs was comparable to the scientific ecological knowledge. Therefore, it is an extremely valuable source of knowledge. The study results suggested that traditional ecological knowledge regarding dugongs directly influences dugong conservation with the dugong being an important indicator of the abundance of aquatic resources. Moreover, the use of the traditional ecological knowledge not only empowered the coastal villagers to participate in dugong conservation, but also supported their participation in dugong planning because the coastal villagers were stakeholders in the co-management.